Positive electrode active material for lithium secondary battery, electrode for lithium secondary battery, and lithium secondary battery
By optimizing the distribution of elements M1 and element M2 on the surface and inside of the positive electrode active material of the lithium secondary battery, an enrichment section is formed, which solves the problem of high lithium ion conductivity resistance and improves the discharge capacity of the battery.
Patent Information
- Application Number
- CN202380063577.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-07
- Filing Date
- 2023-09-01
- Publication Date
- 2025-04-11
AI Technical Summary
The positive electrode active material of the conventional lithium secondary battery is provided with a reaction suppression part on the surface, resulting in a high lithium ion conductivity resistance and a high charge and discharge capacity that is easily reduced.
The secondary particles containing elements M1 and M2 are used to ensure excellent distribution of elements M1 and M2 on the surface and inside by X-ray photoelectron spectroscopy, and an enrichment portion is formed to improve lithium ion conductivity.
The smooth movement of lithium ions in the positive electrode active substance is achieved, and the discharge capacity of the lithium secondary battery is improved.
Smart Images

Figure BDA0005295822280000331 
Figure HDA0005295822290000011 
Figure HDA0005295822290000012
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode active material for a lithium secondary battery, an electrode for a lithium secondary battery, and a lithium secondary battery.
[0002] This application claims priority based on Japanese Tokugan Application No. 2022-142158 filed in Japan on September 7, 2022, and the contents are incorporated herein by reference. Background Art
[0003] As a lithium secondary battery, there is known a battery having a structure including a positive electrode having a positive electrode active material, a negative electrode, and an electrolyte in contact with the positive electrode and the negative electrode.
[0004] As electrolytes used in lithium secondary batteries, electrolyte solutions and solid electrolytes containing organic solvents are known. In the following description, electrolyte solutions and solid electrolytes may be collectively referred to as "electrolyte".
[0005] At the interface between the positive electrode and the electrolyte, the positive electrode active material of the positive electrode contacts the electrolyte. In lithium secondary batteries, lithium ions are deintercalated from the positive electrode active material to the electrolyte and intercalated from the electrolyte to the positive electrode active material in accordance with the charge and discharge of the battery. Therefore, the surface properties of the positive electrode active material are closely related to the intercalation and deintercalation of lithium ions.
[0006] On the other hand, it is known that when the positive electrode active material is in direct contact with the electrolyte, side reactions will occur during charging and discharging, and the battery characteristics will be reduced. As a side reaction, when the electrolyte is an electrolyte, for example, a reaction that generates gas due to oxidative decomposition of the electrolyte can be cited. The generated gas will cause the battery to swell.
[0007] In addition, when the electrolyte is a solid electrolyte, for example, a side reaction may be that the solid electrolyte deteriorates at the contact point between the positive electrode active material and the solid electrolyte to form a resistance layer. The resistance layer formed may hinder the migration of lithium ions. Here, the "resistance layer" refers to, for example, a layer that does not have lithium ion conductivity.
[0008] In order to prevent the battery characteristics from deteriorating, a method of providing a reaction suppression unit having lithium ion conductivity between the positive electrode active material and the electrolyte has been studied. The reaction suppression unit protects the positive electrode active material and suppresses the above-mentioned side reactions. For example, Patent Document 1 discloses an active material particle having a reaction suppression unit formed of lithium niobate on the surface.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2010-170715 Summary of the invention
[0012] Problems to be solved by the invention
[0013] As described in Patent Document 1, when a reaction suppression unit is provided on the surface of the positive electrode active material, the above-mentioned side reactions are less likely to occur. However, the lithium ion conduction resistance of the surface of the positive electrode active material having the reaction suppression unit is high, and there is a tendency that the charge and discharge capacity is easily reduced. Therefore, there is room for further improvement in order to exhibit high capacity while suppressing side reactions.
[0014] The present invention is made in view of the above situation, and its purpose is to provide a positive electrode active material for lithium secondary batteries, which has a compound with excellent lithium ion conductivity on the surface and inside of secondary particles, and lithium ions can move smoothly and have a high discharge capacity. Furthermore, the purpose is to provide a lithium secondary battery electrode and a lithium secondary battery using the positive electrode active material for lithium secondary batteries.
[0015] Means used to solve problems
[0016] In order to solve the above-mentioned problems, the present invention includes the following aspects.
[0017] [1] A positive electrode active material for a lithium secondary battery, comprising secondary particles as aggregates of primary particles, having a layered structure, and comprising an element M1 and an element M2, wherein the element M1 is at least one element selected from the group consisting of Nb, W, Mo, Ta, La, B and P, and the element M2 is at least one element selected from the group consisting of Ni, Co and Mn, and the positive electrode active material for a lithium secondary battery satisfies the following (1) and (2).
[0018] (1) The ratio of the atomic concentration (atomic %) of the element M1 present on the surface of the secondary particle to the total atomic concentration (atomic %) of the element M2 and the element M1 present on the surface of the secondary particle, i.e., α, is greater than 0.6 and less than 1, as obtained by X-ray photoelectron spectroscopy (XPS).
[0019] (2) The ratio of the atomic concentration (atomic %) of the element M1 present inside the secondary particle to the total atomic concentration (atomic %) of the element M2 present inside the secondary particle and the atomic concentration (atomic %) of the element M1, i.e., β, obtained by the X-ray photoelectron spectroscopy (XPS) analysis, is greater than 0.08 and less than 0.20.
[0020] [2] The positive electrode active material for a lithium secondary battery according to [1], wherein the grain boundary of the primary particles in the cross section of the secondary particles observed by transmission electron microscopy - energy dispersive X-ray spectroscopy has an enrichment portion of the element M1.
[0021] [3] The positive electrode active material for a lithium secondary battery according to [1] or [2], wherein the content of Mn is 0.03 mol or more with respect to 1 mol of the total amount of the element M2.
[0022] [4] The positive electrode active material for a lithium secondary battery according to any one of [1] to [3] is represented by the following compositional formula (I).
[0023] Li x (Ni a Co b Mn c Z d M1 e )O δ (I)
[0024] (The compositional formula (I) satisfies 0.98 ≤ x ≤ 1.80, 0.3 < a ≤ 1, 0 ≤ b ≤ 0.3, 0.03 ≤ c ≤ 0.7, 0 ≤ d ≤ 0.05, 0 < e ≤ 0.05, a + b + c + d + e = 1, and 2 ≤ δ < 3. Z is at least one element selected from the group consisting of Al, Zr, and Ti, and M1 is at least one element selected from the group consisting of Nb, W, Mo, Ta, La, B, and P.)
[0025] [5] The positive electrode active material for a lithium secondary battery according to any one of [1] to [4], wherein the ratio S of the atomic concentration of Li present on the surface of the secondary particles to the atomic concentration of the element M1 present on the surface of the secondary particles, obtained by the above-mentioned X-ray photoelectron spectroscopy (XPS) analysis Li is 1 or more and 4 or less.
[0026] [6] The positive electrode active material for a lithium secondary battery according to any one of [1] to [5], wherein the ratio I of the atomic concentration of Li present inside the secondary particles to the atomic concentration of the element M1 present inside the secondary particles, obtained by the above-mentioned X-ray photoelectron spectroscopy (XPS) analysis Li is 10 or more and 50 or less.
[0027] [7] The positive electrode active material for a lithium secondary battery according to any one of [1] to [6], wherein the BET specific surface area is 0.2 m 2 / g or more and 2 m 2 / g or less.
[0028] [8] The positive electrode active material for a lithium secondary battery according to any one of [1] to [7], wherein D 10 , D 50 and D 90 Satisfies the following (II).
[0029] (D 90 -D 10 ) / D 50 ≤1.0(II)
[0030] (D 10 is the 10% cumulative volume particle size of the positive electrode active material for the lithium secondary battery, D 50 D is the 50% cumulative volume particle size of the positive electrode active material for the lithium secondary battery. 90 It is 90% of the cumulative volume particle size of the positive electrode active material for the aforementioned lithium secondary battery.)
[0031] [9] The positive electrode active material for a lithium secondary battery according to any one of [1] to [8], which is for a solid-state lithium secondary battery.
[0032]
[10] A lithium secondary battery electrode comprising the positive electrode active material for a lithium secondary battery according to any one of [1] to [9].
[0033]
[11] A lithium secondary battery comprising the lithium secondary battery electrode according to
[10] .
[0034] Effects of the Invention
[0035] According to the present invention, a positive electrode active material for a lithium secondary battery can be provided, which has a compound with excellent lithium ion conductivity on the surface and inside of secondary particles, and lithium ions can move smoothly and have a high discharge capacity. Furthermore, a lithium secondary battery electrode and a lithium secondary battery using the positive electrode active material for a lithium secondary battery can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 It is a schematic diagram showing an example of a lithium secondary battery.
[0037] Figure 2 It is a schematic diagram showing an example of an all-solid-state lithium secondary battery. DETAILED DESCRIPTION
[0038] In this specification, the metal composite compound (Metal Composite Compound) is hereinafter referred to as "MCC".
[0039] Hereinafter, cathode active material for lithium secondary batteries is referred to as “CAM”.
[0040] The CAM of the present embodiment includes secondary particles which are aggregates of primary particles and has a layered structure.
[0041] The CAM in this embodiment is an aggregate of a plurality of particles. One form of the CAM in this embodiment is in a powder form. In this embodiment, the aggregate of a plurality of particles may include only secondary particles or may be a mixture of primary particles and secondary particles.
[0042] In the present embodiment, the “primary particles” refer to particles that have no apparent grain boundaries when observed using a scanning electron microscope or the like at a viewing angle of 1000 to 30000 times.
[0043] In the present specification, "secondary particles" refer to particles in which a plurality of the above-mentioned primary particles are aggregated three-dimensionally with gaps therebetween. In other words, secondary particles are aggregates of primary particles.
[0044] Unless otherwise specified, the term "Li" refers to Li element rather than Li metal alone. The same applies to other elements such as Ni, Co, Mn, Nb, W, Mo, Ta, La, B, and P.
[0045] When a numerical range is described as, for example, “1-10 μm” or “1 to 10 μm”, it means a range from 1 μm to 10 μm, and indicates a numerical range including 1 μm as a lower limit and 10 μm as an upper limit.
[0046] <Positive electrode active material for lithium secondary battery>
[0047] The CAM of this embodiment includes an element M1 and an element M2.
[0048] The element M1 is at least one element selected from the group consisting of Nb, W, Mo, Ta, La, B and P, and the element M2 is at least one element selected from the group consisting of Ni, Co and Mn. The element M1 is preferably at least one element selected from the group consisting of Nb, W and B, and the element M2 preferably includes Ni and at least one selected from the group consisting of Co and Mn.
[0049] The element M1 of the CAM of this embodiment is present on the surface and inside of the secondary particle. An example of the inside of the secondary particle is the grain boundary between the primary particles. In the case where the element M1 is present on the surface of the secondary particle, the presence of the element M1 can function as a protective film that suppresses side reactions. In the case where the element M1 is present inside the secondary particle, the lithium ion conductivity inside the secondary particle is improved at the presence of the element M1.
[0050] The present invention optimizes the partial state of the element M1 on the surface and inside of the secondary particles.
[0051] Specifically, the element M1 and the element M2 of the CAM of the present embodiment exist at a specific ratio on the surface of the secondary particle and inside the secondary particle. (1)
[0053] The CAM of this embodiment has α defined below in the range of 0.6-1.
[0054] α is the ratio of the atomic concentration (atomic %) of the element M1 present on the surface of the secondary particle to the total amount (element M1 + element M2) of the atomic concentration (atomic %) of the element M1 and the atomic concentration (atomic %) of the element M2 present on the surface of the secondary particle. That is, α is the atomic concentration ratio "element M1 / (element M1 + element M2)" on the surface of the secondary particle.
[0055] In this specification, the “surface” of the secondary particle refers to a range of about 10 nm from the surface of the secondary particle included in the CAM to the center of the particle in the depth direction.
[0056] The value of α is preferably 0.65 or more, more preferably 0.70 or more, and even more preferably 0.74 or more. It is also preferably 0.98 or less, more preferably 0.96 or less, and even more preferably 0.95 or less.
[0057] The above upper limit and lower limit may be arbitrarily combined. In this embodiment, it is preferably 0.65-0.98, more preferably 0.70-0.96, and even more preferably 0.75-0.95.
[0058] When α is equal to or greater than the above lower limit, the ratio of the element M2 contained in the CAM and exposed on the surface of the secondary particle is small. In this case, it becomes easy to suppress the decomposition of the CAM between the CAM and the electrolyte, and a high discharge capacity can be obtained.
[0059] If α is below the above upper limit, it means that the depth of the area containing element M1 on the surface of the secondary particles contained in the CAM is shallow. During the charge and discharge reaction, the valence state of the ions of element M2 changes, and the lithium ions move between the electrolyte and the CAM. At this time, when α is below the above upper limit, the distance between the ions of element M2 and the electrolyte is short, that is, the migration distance of the lithium ions is short and easy to diffuse. Lithium ions that are easily diffused can easily enter the interior from the surface of the secondary particles, and it is easy to obtain a high discharge capacity.
[0060] [Measurement method of α]
[0061] Element M1 and element M2 exist on the surface of secondary particles of CAM. Therefore, when X-ray photoelectron spectroscopy (XPS) analysis of CAM is performed, photoelectrons corresponding to the bonding energy of element M1 and element M2 will be detected. The atomic concentrations of element M1 and element M2 on the surface of secondary particles are obtained by using the analysis results of XPS. Specifically, XPS analysis of CAM is performed under the following conditions, and the peaks corresponding to each element are identified based on the narrow scan spectrum of the obtained CAM. It should be noted that the peak is identified after charge correction is performed with the peak of the CC bond derived from C1s at 286.4 eV.
[0062] Determination method: X-ray photoelectron spectroscopy (XPS)
[0063] X-ray source: AlKα ray (1486.6eV)
[0064] X-ray spot diameter: 100μm
[0065] Pass Energy: 112eV
[0066] Step size: 0.1eV
[0067] Dwell time: 50ms
[0068] Neutralization conditions: Neutralized electron gun (acceleration voltage adjusted by element, current 100μA)
[0069] As the X-ray photoelectron spectrometer, for example, PHI5000VersaProbe III manufactured by ULVAC-PHI, Inc. can be used.
[0070] The detection depth of XPS under the above conditions is within a range of about 10 nm in the depth direction from the surface of the CAM toward the center of the particle.
[0071] The peaks corresponding to each element can be identified using existing databases.
[0072] As for the photoelectron intensity of Nb as the element M1, the integrated value of the waveform of Nb3d is used.
[0073] As for the photoelectron intensity of Ta which is the element M1, the integrated value of the waveform of Ta4f is used.
[0074] As for the photoelectron intensity of Mo as the element M1, the integrated value of the waveform of Mo3d is used.
[0075] As for the photoelectron intensity of B which is the element M1, the integrated value of the waveform of B1s is used.
[0076] As for the photoelectron intensity of P which is the element M1, the integrated value of the waveform of P2p is used.
[0077] As for the photoelectron intensity of W which is the element M1, the integrated value of the waveform of W4f or W4d is used.
[0078] As for the photoelectron intensity of La as the element M1, the integrated value of the waveform of La3d is used.
[0079] Regarding the photoelectron intensity of Ni as the element M2, the integrated value of the waveform of Ni2p3 / 2 is used.
[0080] Regarding the photoelectron intensity of Co as the element M2, the integrated value of the waveform of Co2p3 / 2 is used.
[0081] Regarding the photoelectron intensity of Mn as the element M2, the integrated value of the waveform of Mn2p1 / 2 is used.
[0082] As the photoelectron intensity of Li, the integrated value of the waveform of Li1s was used.
[0083] As the photoelectron intensity of O, the integrated value of the waveform of O1s was used.
[0084] When an element peak overlaps with a peak of another element, the atomic concentration of the corresponding element is calculated by using another orbital peak.
[0085] The atomic concentrations of element M1, element M2, and Li are calculated as follows. First, the converted atomic number of each element is calculated by combining the integral value of the photoelectron peak of each element with the sensitivity coefficient inherent in the device. Then, the atomic concentration is calculated by combining the converted atomic numbers. In the case where the CAM has multiple elements M1 or elements M2, the atomic concentration of element M1 or the atomic concentration of element M2 is the total value of the atomic concentrations of each element M1 or each element M2.
[0086] The atomic concentration (atomic %) of the element M1 was calculated by the following formula.
[0087] Atomic concentration of element M1 = (converted atomic number of element M1 / (converted atomic number of element M2 + converted atomic number of element M1 + converted atomic number of Li + converted atomic number of O))
[0088] The atomic concentration (atomic %) of the element M2 is calculated using the following formula.
[0089] Atomic concentration of element M2 = (converted atomic number of element M2 / (converted atomic number of element M2 + converted atomic number of element M1 + converted atomic number of Li + converted atomic number of O))
[0090] The atomic concentration (atomic %) of Li was calculated by the following formula.
[0091] Atomic concentration of Li = (converted atomic number of Li / (converted atomic number of element M2 + converted atomic number of element M1 + converted atomic number of Li + converted atomic number of O))
[0092] α is calculated from the calculated atomic concentration of the element M1 and the calculated atomic concentration of the element M2. (2)
[0094] The CAM of the present embodiment has β defined below in the range of 0.08 to 0.20.
[0095] β is the ratio of the atomic concentration (atomic %) of the element M1 present inside the secondary particle to the total atomic concentration (atomic %) of the element M1 and the atomic concentration (atomic %) of the element M2 present inside the secondary particle (element M1 + element M2). That is, β is the atomic concentration ratio "element M1 / (element M1 + element M2)" inside the secondary particle.
[0096] β is preferably 0.08 or more, more preferably 0.09 or more, and is preferably 0.18 or less, more preferably 0.15 or less.
[0097] The above upper limit and lower limit may be combined arbitrarily. In this embodiment, it is preferably 0.08-0.18, and more preferably 0.09-0.15.
[0098] A CAM in which β is greater than the above lower limit value indicates that a compound having excellent lithium ion conductivity and containing element M1 is appropriately present inside the secondary particle. In this case, during the charge and discharge reaction, lithium ions move from the surface of the CAM to the inside via the compound having excellent lithium ion conductivity and containing element M1 present inside the secondary particle of the CAM, and the charge and discharge reaction is easy to proceed smoothly, thereby being able to increase the discharge capacity of the lithium ion battery.
[0099] In addition, if β is below the above upper limit, it means that the ratio of the continuous connection between the ions of the element M2 inside the secondary particles of CAM is high. The ions of the element M2 are accompanied by valence changes during the charge and discharge reactions inside the secondary particles of CAM. If the ions of the element M2 are continuously connected, electrons can move with the help of the ions of the element M2 with variable valence, which can increase the discharge capacity of the lithium ion battery.
[0100] [Measurement method of β]
[0101] The elements M1 and M2 of the CAM of this embodiment also exist inside the secondary particles of the CAM. Therefore, by XPS analysis of the CAM subjected to the Ar ion sputtering treatment described below, photoelectrons corresponding to the bonding energy of the elements M1 and M2 inside the secondary particles can be detected.
[0102] In this specification, "the inside of the secondary particles of the CAM" refers to the area exposed by Ar ion sputtering of the secondary particles in the CAM using an XPS internal device under the same conditions as the sputtering to a depth of 100 nm in the case of the SiO2 film. The etching rate is, for example, about 25 nm / min for the SiO2 film.
[0103] The same XPS analysis and calculation of the atomic concentration of each element as in the above-mentioned [method for determining α] are performed on the inside of the secondary particles of the CAM exposed by the above-mentioned Ar ion sputtering treatment. Thus, the atomic concentration of the element M2 present inside the secondary particles and the atomic concentration of the element M1 present inside the secondary particles can be obtained. By calculating the ratio thereof, β can be obtained. (3)
[0105] The CAM of this embodiment preferably has the following definition of S Li Satisfies 1-4.
[0106] S Li is the ratio of the atomic concentration of Li existing on the surface of the secondary particles to the atomic concentration of the element M1 existing on the surface of the secondary particles obtained by the XPS analysis described above. Li It is the atomic concentration ratio "Li / element M1" on the surface of the secondary particle.
[0107] S Li It is more preferably 1.2 or more, further preferably 1.4 or more, and particularly preferably 1.6 or more. Li It is more preferably 3.8 or less, further preferably 3.6 or less, and particularly preferably 3.4 or less.
[0108] S Li The above upper and lower limits can be combined arbitrarily.
[0109] As an example of combination, S Li Are 1.2-3.8, 1.4-3.6, 1.6-3.4.
[0110] S Li When the content is at least the above lower limit, the lithium ion conductivity is excellent and a CAM having a high discharge capacity is easily obtained.
[0111] In addition, S Li When it is below the upper limit, CAM with less surface residues such as lithium carbonate and lithium hydroxide is likely to be formed, and as a result, the discharge capacity is likely to be increased.
[0112] S Li It can be calculated from the atomic concentration of the element M1 and the atomic concentration of Li calculated in the same procedure as in the above-mentioned [Measurement method of α]. (4)
[0114] The CAM of this embodiment is preferably defined as follows: Li Is 10-50.
[0115] I Li is the ratio of the atomic concentration of Li existing inside the secondary particle to the atomic concentration of the element M1 existing inside the secondary particle obtained by the aforementioned XPS analysis. Li It is the atomic concentration ratio "Li / element M1" inside the secondary particle.
[0116] I Li It is more preferably 12 or more, and even more preferably 14 or more. Li It is more preferably 45 or less, and even more preferably 40 or less.
[0117] I Li The above upper and lower limits can be combined arbitrarily.
[0118] As an example of combination, I Li 12-45, 14-40.
[0119] I Li When the content is not less than the above lower limit, Li is concentrated in the interior of the secondary particle, lithium ion conductivity is excellent, and a CAM having a high discharge capacity is easily obtained.
[0120] In addition, I Li When the content is equal to or less than the upper limit, the element M1 that assists in the conduction of lithium ions is sufficiently present, the lithium ion conductivity is excellent, and a CAM having a high discharge capacity is easily obtained.
[0121] I LiIt can be calculated from the atomic concentration of the element M1 and the atomic concentration of Li calculated in the same procedure as in the above-mentioned [Measurement method of β].
[0122] Enrichment Department
[0123] The CAM of the present embodiment preferably has a portion enriched in the element M1 at a grain boundary of a primary particle in a cross section of a secondary particle observed by transmission electron microscopy-energy dispersive X-ray spectroscopy.
[0124] “Element M1-enriched portions are present at the grain boundaries of primary particles” means that element M1-enriched portions are present on the surface of primary particles or in gaps between primary particles. When the enriched portions are present on the surface of primary particles, element M1 may be present as a solid solution on the surface of the primary particles.
[0125] When the enriched portion exists in the gaps between the primary particles, the compound containing the element M1 may exist in the grain boundaries between the primary particles.
[0126] The cross section of the secondary particle can be obtained by the following method.
[0127] [How to obtain the cross section]
[0128] In this specification, the "cross section" of a secondary particle refers to a region exposed when a CAM is subjected to thin-section processing using a focused ion beam (FIB).
[0129] [Method for confirming the enriched fraction]
[0130] The grain boundaries and the concentrated areas can be confirmed, for example, by a conventional transmission electron microscope (TEM)-energy dispersive X-ray spectroscopy (EDX) method.
[0131] Specifically, the cross section obtained in the above-mentioned [Method for Obtaining Cross Section] is observed by TEM at an appropriate magnification. In the obtained TEM observation image, for example, for adjacent primary particles A and primary particles B, surface analysis is continuously performed using EDX from the inside of primary particle A to the inside of primary particle B to obtain the concentration ratio of element M1 to element M2, i.e., E1.
[0132] Next, the ratio of element M1 to element M2, i.e., E2, is determined when the surface of the interior of the primary particle, i.e., the region not sandwiched by the grain boundary, is analyzed by EDX. The enriched portion is considered to exist when the ratio E1 / E2 is greater than 1. The enriched portion is considered to exist when the ratio E1 / E2 is less than 1.
[0133] The presence of the element M1-enriched portion at the grain boundary of the primary particles constituting the secondary particles allows lithium ions to be smoothly inserted and removed along the enriched portion. In this case, the utilization rate of CAM in the positive electrode is improved, the resistance is easily reduced, and the discharge capacity is improved.
[0134] As a transmission electron microscope, for example, JEM-2100F manufactured by JEOL Ltd. can be used. As EDX, Centurio manufactured by JEOL Ltd. can be used.
[0135] 《BET specific surface area》
[0136] The BET specific surface area of CAM is preferably 0.2-2 m 2 / g. The BET specific surface area is more preferably 0.3 m 2 / g or more, more preferably 0.4m 2 / g or more. In addition, the BET specific surface area is more preferably 1.8 m 2 / g or less, more preferably 1.5m 2 / g or less.
[0137] The above-mentioned upper limit value and lower limit value of the BET specific surface area may be combined arbitrarily.
[0138] As an example of a combination, the BET surface area is 0.3-1.8 m 2 / g, 0.4-1.5m 2 / g.
[0139] When a CAM having a BET specific surface area equal to or greater than the above lower limit is used, the number of reaction interfaces of the CAM increases, and lithium ions can easily enter and exit, so that the discharge capacity tends to increase.
[0140] When a CAM having a BET specific surface area below the upper limit is used, the contact area between the CAM and the electrolyte is not easily increased, and a film due to decomposition of the electrolyte is not easily formed. When there is less such a film, the lithium ion conductivity is not easily suppressed, and thus the discharge capacity is easily increased.
[0141] [Measurement of BET specific surface area]
[0142] The BET specific surface area of CAM can be measured using a BET specific surface area measuring device. As a BET specific surface area measuring device, for example, Macsorb (registered trademark) manufactured by Mountech Co., Ltd. can be used. When measuring powdered CAM, it is preferably dried at 105° C. for 30 minutes in a nitrogen atmosphere as a pretreatment.
[0143] D 10 , D 90 and D 50 》
[0144] CAM preferred D 10 , D 90 and D 50 Satisfies the following (II).
[0145] (D 90 -D 10 ) / D 50 ≤1.0(II)
[0146] ((II) in D 10 The 10% cumulative volume particle size of CAM, D 50 The 50% cumulative volume particle size of CAM, D 90 It is the 90% cumulative volume particle size of CAM. )
[0147] D 10 , D 90 and D 50 (II)-1 is preferred, and (II)-2 is more preferred.
[0148] 0.2≤(D 90 -D 10 ) / D 50 ≤0.8 (II)-1
[0149] 0.2≤(D 90 -D 10 ) / D 50 ≤0.6 (II)-2
[0150] The CAM satisfying (II) is easy to fill when manufacturing the positive electrode, and the contact with the conductive auxiliary agent is improved, so the discharge capacity is easily increased.
[0151] [D 10 , D 90 and D 50 Determination of
[0152] In this manual, the D 10 (μm), D 50 (μm) and D 90 (μm) can be measured by the following dry method.
[0153] Specifically, first, 2 g of CAM was used to measure the dry particle size distribution using a laser diffraction particle size analyzer to obtain a volume-based cumulative particle size distribution curve. In the obtained cumulative particle size distribution curve, the values of the particle sizes at 10%, 50%, and 90% cumulatively from the fine particle side are D and D, respectively. 10 , D 50 , D 90 .
[0154] As a laser diffraction particle size distribution analyzer, for example, MS2000 manufactured by Malvern can be used.
[0155] In the CAM of the present embodiment, preferably, relative to 1 mol of the total amount of element M2, the content of Mn is 0.03 mol or more, preferably 0.03 - 0.7 mol.
[0156] If the ratio of Mn is equal to or higher than the aforementioned lower limit value, a lithium secondary battery with high thermal stability will be formed.
[0157] The CAM is preferably represented by the following compositional formula (I).
[0158] Li x (Ni a Co b Mn c Z d M1 e )O δ (I)
[0159] (The compositional formula (I) satisfies 0.98 ≤ x ≤ 1.80, 0.3 < a ≤ 1, 0 ≤ b ≤ 0.3, 0.03 ≤ c ≤ 0.7, 0 ≤ d ≤ 0.05, 0 < e ≤ 0.05, a + b + c + d + e = 1, and 2 ≤ δ < 3. Z is at least one element selected from the group consisting of Al, Zr, and Ti, and M1 is at least one element selected from the group consisting of Nb, W, Mo, Ta, La, B, and P.)
[0160] x preferably satisfies 1.00 ≤ x ≤ 1.60. Further, from the perspective of obtaining a lithium secondary battery with high cycle characteristics, x in the compositional formula (I) is more preferably 1.01 or more, and still more preferably 1.03 or more. In addition, from the perspective of suppressing the formation of the resistance layer, x in the compositional formula (I) is more preferably 1.50 or less, and still more preferably 1.30 or less.
[0161] The upper limit value and the lower limit value of x can be arbitrarily combined.
[0162] As an example of the combination, x is 1.01 - 1.50, 1.03 - 1.30.
[0163] In addition, from the perspective of obtaining a lithium ion secondary battery with a high battery capacity, a in the compositional formula (I) is preferably greater than 0.40, more preferably 0.45 or more, still more preferably 0.50 or more, and particularly preferably 0.55 or more. Further, from the perspective of obtaining a lithium secondary battery with high thermal stability, a in the compositional formula (I) is more preferably 0.98 or less, still more preferably 0.95 or less, and still more preferably 0.90 or less.
[0164] The upper limit and lower limit of a may be arbitrarily combined. In composition formula (I), a may be 0.45-0.98, 0.50-0.95, or 0.55-0.90.
[0165] b preferably satisfies 0≤b≤0.25. In order to obtain a lithium secondary battery with high cycle characteristics, b in the composition formula (I) is more preferably greater than 0, and further preferably greater than 0 and 0.25 or less.
[0166] From the perspective of obtaining a lithium secondary battery with high cycle characteristics, c in the composition formula (I) is preferably 0.05 or more, more preferably 0.10 or more, further preferably 0.20 or more, and particularly preferably 0.25 or more. In addition, from the perspective of obtaining a lithium secondary battery with high storage properties under high temperature (for example, 60°C environment), c in the composition formula (I) is preferably 0.50 or less, more preferably 0.40 or less, and further preferably 0.30 or less.
[0167] The upper limit and lower limit of c may be arbitrarily combined. In composition formula (I), c may be 0.05-0.50, 0.20-0.40, or 0.25-0.30.
[0168] c preferably satisfies 0.05≤c≤0.50.
[0169] Preferably, d satisfies 0≤d≤0.03.
[0170] e preferably satisfies 0 <e≤0.03。
[0171] [Composition Analysis]
[0172] The composition analysis of CAM (composition formula (I), the above-mentioned Mn content) can be performed by dissolving CAM in hydrochloric acid and using an inductively coupled plasma emission spectrometer (for example, SPS3000 manufactured by Seiko Nanotechnologies Corporation).
[0173] (Crystal Structure)
[0174] In the present specification, the "layered structure" refers to a hexagonal crystal structure or a monoclinic crystal structure.
[0175] The hexagonal crystal structure belongs to a group consisting of P3, P31, P32, R3, P-3, R-3, P312, P321, P3112, P3121, P3212, P3221, R32, P3m1, P31m, P3c1, P31c, R3m, R3c, P-31m, P-31c, P-3m1, P-3c1, R-3m, R-3c, P6, P61, P65, P Any space group in the group consisting of P62, P64, P63, P-6, P6 / m, P63 / m, P622, P6122, P6522, P6222, P6422, P6322, P6mm, P6cc, P63cm, P63mc, P-6m2, P-6c2, P-62m, P-62c, P6 / mm, P6 / mcc, P63 / mcm and P63 / mmc.
[0176] In addition, the monoclinic crystal structure belongs to any space group selected from the group consisting of P2, P21, C2, Pm, Pc, Cm, Cc, P2 / m, P21 / m, C2 / m, P2 / c, P21 / c and C2 / c.
[0177] Among these, in order to obtain a lithium secondary battery with a high discharge capacity, the crystal structure is preferably either or both of a hexagonal crystal structure belonging to the space group R-3m and a monoclinic crystal structure belonging to C2 / m.
[0178] [Method for confirming layer structure]
[0179] Whether or not CAM has a layered structure can be confirmed by observing the crystal structure using a powder X-ray diffraction measurement apparatus (for example, Ultima IV manufactured by Rigaku Corporation).
[0180] The surface of the secondary particle of CAM preferably contains a compound containing the element M1 and Li, specifically, lithium lanthanide oxides such as lithium niobate, lithium tantalate, lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, lithium tungstate, lithium phosphate, and lithium borate.
[0181] [Determination of initial discharge capacity]
[0182] In the present embodiment, the initial discharge capacity using the CAM can be measured by the following method.
[0183] This paper describes the evaluation method of initial discharge capacity using solid-state lithium-ion batteries as an example.
[0184] <Manufacturing of solid-state lithium-ion secondary batteries>
[0185] The following operations were performed in a glove box under an argon atmosphere.
[0186] (Fabrication of the positive electrode composite material)
[0187] Weigh 1.000 g of CAM, 0.0543 g of conductive material (acetylene black), and 8.6 mg of solid electrolyte (Li6PS5Cl manufactured by MSE). Mix the CAM, conductive material, and solid electrolyte in a mortar for 15 minutes to fabricate the positive electrode composite material powder.
[0188] (Battery fabrication)
[0189] Put 160 mg of solid electrolyte powder into a polyethylene terephthalate tube (PET tube, inner diameter 10 mm) inserted with a SUS rod (diameter 10 mm). Insert the SUS rod from above and press it at 10 MPa to form a solid electrolyte layer with a diameter of 10 mm. Then, take out the SUS rod inserted from above, put 15 mg of the above positive electrode composite material powder on the solid electrolyte layer, then place a SUS plate (diameter 10 mm) as the current collector foil, and then insert the SUS rod. Further, place an indium foil and a lithium metal foil on the solid electrolyte layer on the side opposite to the positive electrode composite material powder, press it with a single screw at 14 MPa, and then constrain it at 6 MPa to fabricate a solid-state lithium-ion battery.
[0190] (Charge-discharge test)
[0191] Use the solid-state lithium-ion battery fabricated by the above method to conduct a charge-discharge test under the conditions shown below.
[0192] (Charge-discharge conditions)
[0193] Test temperature: 60 °C
[0194] (Charge-discharge)
[0195] Maximum charge voltage 3.68 V, charge current density 0.1 C, cut-off current density 0.02 C, constant current-constant voltage charging
[0196] Minimum discharge voltage 1.88 V, discharge current density 0.1 C, constant current discharge
[0197] If the initial discharge capacity measured by the above method is 172 mAh / g or more, it is evaluated as "high discharge capacity".
[0198] (Manufacturing method of CAM)
[0199] The manufacturing method of CAM in this embodiment includes a step of introducing the coating material raw material containing element M1 two or more times. Specifically, it includes the following manufacturing process (A) or manufacturing process (B), and a step of mixing the obtained fired product with the coating material raw material containing element M1.
[0200] When manufacturing a CAM, first, an MCC containing at least one element M2 selected from the group consisting of Ni, Co, and Mn is prepared, and preferably, the MCC and a suitable lithium compound are fired. As the MCC, a metal composite hydroxide or a metal composite oxide is preferred.
[0201] Hereinafter, an example of the method for manufacturing a CAM will be described by dividing it into an MCC manufacturing step and a CAM manufacturing step.
[0202] (MCC manufacturing step)
[0203] The MCC can be manufactured by a conventionally well-known coprecipitation method. As the coprecipitation method, a conventionally well-known batch coprecipitation method or a continuous coprecipitation method can be used. Hereinafter, taking a metal composite hydroxide containing Ni, Co, and Mn as an example, the method for manufacturing the MCC will be described in detail.
[0204] First, a nickel salt solution, a cobalt salt solution, a manganese salt solution, and a complexing agent are reacted by a coprecipitation method, particularly the continuous coprecipitation method described in JP-A2002-201028, to manufacture a metal composite hydroxide represented by Ni a Co b Mn c (OH)2 (where 0 < a + b + c ≤ 1).
[0205] Regarding the nickel salt as the solute of the above nickel salt solution, there is no particular limitation, and for example, any one or two or more of nickel sulfate, nickel nitrate, nickel chloride, and nickel acetate can be used.
[0206] Regarding the cobalt salt as the solute of the above cobalt salt solution, for example, any one or two or more of cobalt sulfate, cobalt nitrate, cobalt chloride, and cobalt acetate can be used.
[0207] Regarding the manganese salt as the solute of the above manganese salt solution, for example, any one or two or more of manganese sulfate, manganese nitrate, manganese chloride, and manganese acetate can be used.
[0208] The above metal salts are used in a ratio corresponding to the composition ratio of the above Ni a Co b Mn c (OH)2. That is, the molar ratio of each metal salt to Ni in the solute of the nickel salt solution, Co in the solute of the cobalt salt solution, and Mn in the solute of the manganese salt solution is Ni a Co b Mn c (OH)2, and amounts forming a:b:c are used correspondingly.
[0209] In addition, the solvents of the nickel salt solution, the cobalt salt solution, and the manganese salt solution are water. That is, the solvents of the nickel salt solution, the cobalt salt solution, and the manganese salt solution are aqueous solutions.
[0210] The complexing agent is a compound that can form a complex with nickel ions, cobalt ions and manganese ions in an aqueous solution. Examples of the complexing agent include ammonium ion donors (ammonium salts such as ammonium hydroxide, ammonium sulfate, ammonium chloride, ammonium carbonate, and ammonium fluoride), hydrazine, ethylenediaminetetraacetic acid, nitrilotriacetic acid, uracildiacetic acid, and glycine.
[0211] When a complexing agent is used, the amount of the complexing agent contained in the mixed solution comprising a nickel salt solution, an arbitrary metal salt solution, and the complexing agent is, for example, a molar ratio relative to the total number of moles of the metal salt greater than 0 and less than 2.0. The amount of the complexing agent contained in the mixed solution comprising a nickel salt solution, a cobalt salt solution, a manganese salt solution, and the complexing agent is, for example, a molar ratio relative to the total number of moles of the metal salt greater than 0 and less than 2.0.
[0212] In the coprecipitation method, in order to adjust the pH of the mixed solution containing the nickel salt solution, the optional metal salt solution and the complexing agent, an alkali metal hydroxide is added to the mixed solution before the pH of the mixed solution changes from alkaline to neutral. The alkali metal hydroxide is, for example, sodium hydroxide or potassium hydroxide.
[0213] In addition, the pH value in this specification is defined as a value measured when the temperature of the mixed liquid is 40° C. The pH of the mixed liquid is measured when the temperature of the mixed liquid sampled from the reaction tank reaches 40° C.
[0214] If a complexing agent is continuously supplied to the reaction tank in addition to the above-mentioned nickel salt solution, cobalt salt solution, and manganese salt solution, Ni, Co, and Mn react to generate Ni a Co b Mn c (OH)2.
[0215] During the reaction, the temperature of the reaction tank is controlled within the range of, for example, 20-80°C, preferably 30-70°C.
[0216] During the reaction, the pH value in the reaction tank is controlled within the range of, for example, pH 9-13, preferably pH 11-13.
[0217] The contents of the reaction tank are stirred appropriately to mix.
[0218] The reaction tank used in the continuous coprecipitation method may be an overflow type reaction tank in order to separate the formed reaction precipitate.
[0219] In addition to the control of the above conditions, various gases, for example, inert gases such as nitrogen, argon, and carbon dioxide, oxidizing gases such as air and oxygen, or mixed gases thereof may be supplied into the reaction vessel.
[0220] Specifically, the reaction tank may be in an inert atmosphere. If the reaction tank is in an inert atmosphere, it is possible to suppress the aggregation of elements contained in the mixed solution that are more easily oxidized than Ni than Ni. Therefore, a uniform metal composite hydroxide can be obtained.
[0221] After the above reaction, the obtained reaction precipitate is washed with water and then dried to obtain MCC. In the present embodiment, nickel-cobalt-manganese hydroxide can be obtained as MCC. In addition, in the case where only washing with water leaves inclusions originating from the mixed solution in the reaction precipitate, the reaction precipitate can be washed with weak acid water or an alkaline solution as required. As the alkaline solution, an aqueous solution containing sodium hydroxide or potassium hydroxide can be cited.
[0222] It should be noted that, in the above examples, nickel-cobalt-manganese composite hydroxides were produced, but nickel-cobalt-manganese composite oxides may also be produced.
[0223] In the case of manufacturing MCC as a metal composite oxide, the metal composite oxide can be manufactured by oxidizing a metal composite hydroxide. For example, a nickel-cobalt-manganese composite oxide can be prepared by oxidizing a nickel-cobalt-manganese composite hydroxide. When preparing the metal composite oxide, the oxidation can be performed at a temperature of 300-800° C. in the range of 1-30 hours.
[0224] The temperature increase rate during oxidation is preferably 180° C. / hour or more, more preferably 200° C. / hour or more, and particularly preferably 250° C. / hour or more.
[0225] In addition, the reaction tank may be in a moderate oxidizing atmosphere. The oxidizing atmosphere may be an oxygen-containing atmosphere obtained by mixing an oxidizing gas into an inert gas, or an oxidant may be present under an inert gas atmosphere. By making the reaction tank in a moderate oxidizing atmosphere, it becomes easy to control the morphology of the metal composite oxide.
[0226] The oxygen or oxidizing agent in the oxidizing atmosphere may contain sufficient oxygen atoms to oxidize the transition metal element.
[0227] As the oxidizing agent, peroxides such as hydrogen peroxide, peroxide salts such as permanganate, perchlorates, hypochlorites, nitric acid, halogens, ozone, and the like can be used.
[0228] When the oxidizing atmosphere is an oxygen-containing atmosphere, the atmosphere in the reaction vessel can be controlled by a method such as introducing an oxidizing gas into the reaction vessel or bubbling an oxidizing gas into the mixed liquid.
[0229] (CAM manufacturing process)
[0230] The CAM of the present embodiment can be obtained by a production method including the following production step (A) or production step (B), using a coating material raw material containing the element M1, and mixing the obtained fired product with the coating material raw material containing the element M1.
[0231] Production step (A): a step of obtaining a mixture containing MCC, a coating material raw material including the element M1, and a lithium compound, and a step of firing the mixture to obtain a fired product.
[0232] Production step (B): a step of primary-firing a mixture of MCC and a lithium compound to obtain a primary fired product, and a step of mixing the primary fired product with a coating material raw material containing the element M1 and mainly firing the mixture to obtain a fired product.
[0233] One embodiment of the process for producing CAM includes a production step (A) and a step of mixing the obtained fired product with a coating material raw material containing the element M1.
[0234] One embodiment of the process for producing CAM includes the production step (B) and the step of mixing the obtained fired product with a coating material raw material containing the element M1.
[0235] [Manufacturing process (A)]
[0236] (Step of Obtaining a Mixture Containing MCC, a Coating Material Raw Material Containing the Element M1, and a Lithium Compound)
[0237] First, MCC, a coating material raw material containing element M1, and a lithium compound are mixed to obtain a mixture containing MCC, a coating material raw material containing element M1, and a lithium compound. For example, a method of adding and mixing the coating material raw material to MCC and then mixing the lithium compound to obtain the mixture can be cited.
[0238] The mixing method of MCC and the coating material raw material can be either a dry method or a wet method, and the wet method is more preferred. In the case of mixing MCC and the coating material raw material by a wet method, a drying step can be further performed. By mixing MCC and the coating material raw material by a wet method, it is easy to form an M1-enriched portion at the grain boundary of the primary particle inside the secondary particle.
[0239] If a wet method is used, the dispersibility of the coating material raw material into the secondary particles of CAM can be improved, and aggregation of the coating material raw material can be prevented. In the wet method, the above effects can be enhanced by mixing, stirring and drying MCC and the coating material raw material in the same process.
[0240] The coating material raw material is a material containing at least one element M1 selected from the group consisting of Nb, Ta, B, Mo, W, La, and P.
[0241] In the case of a wet method, the coating material raw material is preferably an additive solution containing a Li source, an element M1 source and a solvent. Examples of the element M1 source include oxides, hydroxides, carbonates, nitrates, sulfates, halides, oxalates, alkoxides or complexes of the element M1.
[0242] Examples of the Li source include Li alkoxides, Li inorganic salts, and Li hydroxides.
[0243] Examples of the Li alkoxide include lithium ethoxide and lithium methoxide.
[0244] Examples of the Li inorganic salt include lithium nitrate, lithium sulfate, and lithium acetate. Examples of the Li hydroxide include lithium hydroxide and lithium hydroxide hydrate.
[0245] When the element M1 is Nb, examples of the Nb source include Nb alkoxides, Nb inorganic salts, Nb hydroxides, and Nb complexes.
[0246] Examples of the Nb alkoxide include niobium pentaethoxide, niobium pentamethoxide, niobium pentaisopropoxide, niobium penta-n-propoxide, niobium pentaisobutoxide, niobium penta-n-butoxide, and niobium penta-sec-butoxide.
[0247] Examples of the Nb inorganic salt include niobium acetate, etc. As niobium oxide, a hydrate can be used.
[0248] Examples of the Nb hydroxide include niobium hydroxide.
[0249] Examples of the Nb complex include peroxo complexes of Nb (peroxoniobate complex, [Nb(O2)4] 3- ).
[0250] The additive solution containing the Nb peroxo complex has an advantage in that the amount of gas generated is smaller than that of the additive solution containing the Nb alkoxide.
[0251] As a method for preparing the solution containing the Nb peroxo complex, for example, there is a method of adding hydrogen peroxide and ammonia to Nb oxide or Nb hydroxide. The amounts of hydrogen peroxide and ammonia added may be appropriately adjusted to obtain a transparent solution (homogeneous solution).
[0252] When the element M1 is Ta, tantalum oxide can be cited as a Ta source.
[0253] When the element M1 is B, examples of the B source include boron oxide.
[0254] When the element M1 is Mo, examples of the Mo source include molybdenum oxide.
[0255] When the element M1 is W, examples of the W source include tungsten oxide and lithium tungstate.
[0256] When the element M1 is La, examples of the La source include lanthanum oxide.
[0257] When the element M1 is P, examples of the P source include diammonium hydrogen phosphate and ammonium dihydrogen phosphate.
[0258] The type of solvent to be added to the solution is not particularly limited, and examples thereof include alcohol and water.
[0259] Examples of alcohol include methanol, ethanol, propanol, butanol, etc. When the added solution contains Nb alkoxide, the solvent is preferably anhydrous or dehydrated alcohol. On the other hand, when the added solution contains a peroxo complex of Nb, for example, the solvent is preferably water.
[0260] When MCC is mixed with the coating material raw material, the mixing device is not limited as long as it can be mixed uniformly. For example, it is preferable to use a Redige Mixer or a rotary flow device for mixing. These devices can spray and mix the coating material raw material while flowing MCC, and stir and dry it. For example, the rotary flow device can be preferably MP-01 manufactured by Powrex Corporation.
[0261] MCC can be used in the coating material raw material at a ratio corresponding to the composition ratio of the above-mentioned composition formula (I).
[0262] As the lithium compound, any one of lithium carbonate, lithium nitrate, lithium acetate, lithium hydroxide, lithium hydroxide hydrate, lithium oxide, lithium chloride, and lithium fluoride can be used, or a mixture of two or more thereof can be used. Among these, any one or both of lithium hydroxide, lithium hydroxide hydrate, and lithium carbonate are preferred.
[0263] The lithium compound and MCC are used in consideration of the composition ratio of the final target. The lithium compound and the MCC are used in a ratio corresponding to the composition ratio of the above-mentioned composition formula (I). In addition, in the case of an excess of Li (containing a molar ratio greater than 1) in the CAM as the final target, the lithium compound and the MCC are mixed in a ratio such that the molar ratio of Li contained in the lithium compound to the metal element contained in the MCC is greater than 1. Li and I Li The value of is controlled within the range of this embodiment.
[0264] (Step of firing the mixture to obtain a fired product)
[0265] Next, a mixture containing MCC, the coating material raw material, and the lithium compound is fired to obtain a fired product.
[0266] By calcining the mixture, MCC reacts with the lithium compound, primary particles grow, and the primary particles aggregate and sinter to form secondary particles with grain boundaries. Element M1 exists at the grain boundaries of the primary particles, forming a portion rich in element M1.
[0267] For example, a lithium-nickel-cobalt-manganese composite oxide can be obtained by calcining a mixture of a nickel-cobalt-manganese composite compound and a lithium compound. Note that the calcination may be performed in dry air, an oxygen atmosphere, an inert atmosphere, or the like, depending on the desired composition.
[0268] The holding temperature during calcination is specifically in the range of 600-1150° C., preferably 650-1050° C., and more preferably 700-1000° C. The holding time at the holding temperature is 0.1-20 hours, preferably 0.5-10 hours. In addition, the calcination atmosphere can be air, oxygen, nitrogen, argon, or a mixed gas thereof.
[0269] The calcination may be performed multiple times. For example, a mixture containing MCC, a coating material raw material, and a lithium compound may be calcined once, and then a main calcination may be performed at a higher temperature than the primary calcination. The holding temperature and holding time during the primary calcination and the main calcination may be within the range described in the [manufacturing process (B)] described later.
[0270] [Manufacturing process (B)]
[0271] (Step of primary calcining a mixture of MCC and a lithium compound to obtain a primary calcined product)
[0272] The MCC obtained in (MCC production process) is mixed with a lithium compound to obtain a mixture of MCC and a lithium compound. As the lithium compound, the compounds listed in [production process (A)] can be used. The lithium compound and MCC are used in a ratio corresponding to the composition ratio of the above-mentioned composition formula (I).
[0273] Next, the mixture of MCC and the lithium compound is primarily calcined to obtain a primarily calcined product.
[0274] The holding temperature of the primary firing specifically ranges from 300°C to 750°C, preferably from 400°C to 700°C, and more preferably from 450°C to 680°C.
[0275] The time for holding at the holding temperature of the primary firing can be 0.1 hours or more and 20 hours or less, preferably 0.5 hours or more and 10 hours or less. The heating rate to the aforementioned holding temperature is usually 50°C / hour or more and 400°C / hour or less, and the cooling rate from the aforementioned holding temperature to room temperature is usually 10°C / hour or more and 400°C / hour or less. In addition, as the atmosphere for the primary firing, air, oxygen, nitrogen, argon or a mixed gas thereof can be used.
[0276] (Step of mixing the primary fired product with a coating material raw material containing the element M1 and performing main firing to obtain a fired product)
[0277] The coating material raw material containing the element M1 is mixed with the primary fired product, and then main firing is performed to obtain a fired product (main fired product).
[0278] When the primary calcined product is mixed with the coating material raw material, either a dry method or a wet method may be used, preferably a wet method. When the primary calcined product is mixed with the coating material raw material by a wet method, a drying step may be further performed. As the coating material raw material and the mixing device, the materials and the mixing device listed in [manufacturing process (A)] may be listed.
[0279] The primary fired product is a secondary particle having a grain boundary obtained by the reaction of MCC and lithium compound, and the aggregation and sintering of primary particles. The primary fired product is mixed with the coating material raw material and mainly fired to diffuse the element M1 into the grain boundary, forming a portion rich in the element M1.
[0280] The holding temperature during the main calcination is specifically in the range of 600°C to 1150°C, preferably 650°C to 1050°C, and more preferably 700°C to 1000°C.
[0281] In addition, the time of holding at the holding temperature of the main sintering can be listed as 0.1 hours or more and 20 hours or less, preferably 0.5 hours or more and 10 hours or less. The heating rate to the aforementioned holding temperature is usually 50°C / hour or more and 400°C / hour or less, and the cooling rate from the aforementioned holding temperature to room temperature is usually 10°C / hour or more and 400°C / hour or less. In addition, as the atmosphere of the main sintering, air, oxygen, nitrogen, argon or a mixed gas thereof can be used.
[0282] (Optional pulverization step)
[0283] The burned product obtained in the manufacturing step (A) or the manufacturing step (B) is preferably subjected to a pulverization treatment. By pulverizing the burned product, the burned product is pulverized starting from large pores. Therefore, a CAM having a small ratio of large pores can be obtained.
[0284] The fired product may be pulverized, and the pulverized product may be further fired. Alternatively, the pulverized product may be dried.
[0285] By calcining after pulverization, foreign matter such as lithium carbonate generated on the surface of the pulverized product can be removed.
[0286] As a pulverizer used for pulverization treatment, a Masscolloider type pulverizer is mentioned, for example.
[0287] The rotation speed of the pulverizer is preferably in the range of 500-2000 rpm.
[0288] Through the above steps, a burned product (main burned product) can be obtained.
[0289] By using the fired product obtained in the production step (A) or the production step (B), the β, S Li and I Li The value of is controlled within the above range.
[0290] [Step of mixing the fired product with a coating material raw material containing the element M1]
[0291] The burned product obtained by the above-mentioned manufacturing process (A) or manufacturing process (B) (a crushed product in the case of implementing a crushing process) is mixed with a coating material raw material containing the element M1, and heat-treated as needed, thereby obtaining a coated CAM. The mixing method of the burned product and the coating material raw material is preferably a wet method. Specifically, the burned product and the coating material raw material are mixed by spraying the coating material raw material on the burned product. Regarding the coating material raw material and the device during the coating process, the materials and devices listed in [Manufacturing process (A)] can be listed. As a coating method, a wet method using a rotating flow device is preferred, and as a coating material raw material, a material containing Nb is preferred.
[0292] When a rotary flow device is used in the coating process, it is preferred to use a two-fluid spray nozzle that uses high-pressure air to atomize the coating material raw material when adding the coating material raw material. In order to adjust the α and β of the CAM to the above range, it is preferred to control the flow rate of the high-pressure air in the range of 10-80NL / min.
[0293] The sintered product includes secondary particles formed by the aggregation of primary particles. By making the flow rate of high-pressure air below the above upper limit, when the secondary particles are crushed, the newly formed surface inside the secondary particles becomes difficult to be exposed. By making it difficult for the newly formed surface inside the secondary particles without the element M1 to be generated, the values of α and β of CAM can be controlled to be above the lower limit, respectively.
[0294] On the other hand, by setting the flow rate of high-pressure air to be above the lower limit, the diameter of the droplets of the coating material raw material can be uniformly reduced, and the droplets can be uniformly attached to the surface of the fired product, so that α of CAM can be controlled to be above the lower limit.
[0295] Furthermore, by making the flow rate of high-pressure air above the lower limit, the coating material raw material is not easily infiltrated into the secondary particles in the sintered product, and the β of CAM can be controlled below the upper limit. In addition, if the flow rate of high-pressure air is above the lower limit, the aggregation between the secondary particles can be broken up, and if it is below the upper limit, the micronization caused by the crushing of the secondary particles can be suppressed. As a result, (D 90 -D 10 ) / D 50 and the BET specific surface area are adjusted to the range of this embodiment.
[0296] The burned product and the coating material raw material may be mixed at a ratio corresponding to the composition ratio of the above-mentioned composition formula (I).
[0297] After the coating material raw material and the sintered product are mixed, heat treatment may be performed. Heat treatment conditions are adjusted according to the type of coating material raw material. Examples of heat treatment conditions include heat treatment temperature and heat treatment holding time.
[0298] For example, when the coating material raw material contains Nb, it is preferred to perform heat treatment at a temperature range of 200°C to 800°C for 4 hours to 10 hours. If the heat treatment temperature is within the above range, it is possible to prevent the coating material raw material from being dissolved in the sintered product. If the heat treatment time is within the above range, the coating material raw material can be fully diffused into the sintered product.
[0299] The heat treatment temperature in this specification refers to the temperature of the atmosphere in the heating furnace, and is the maximum temperature of the holding temperature in the heat treatment process.
[0300] The coating material raw material and the fired product are mixed and heat treated under the above-mentioned heat treatment conditions, thereby obtaining a CAM.
[0301] CAM can be used for appropriate crushing and grading.
[0302] By going through the manufacturing step (A) or the manufacturing step (B), and mixing the obtained sintered product with a coating material raw material containing the element M1, the element M1 is uniformly present inside or on the surface of the secondary particles of the CAM, thereby obtaining a CAM whose α and β are within the range of this embodiment.
[0303] <Lithium Secondary Battery>
[0304] A preferred positive electrode for a lithium secondary battery when the CAM of the present embodiment is used will be described. Hereinafter, the positive electrode for a lithium secondary battery may be referred to as a positive electrode.
[0305] Furthermore, a lithium secondary battery which is preferable as an application of the positive electrode will be described.
[0306] An example of a preferred lithium secondary battery when using the CAM of the present embodiment includes a positive electrode and a negative electrode, a separator sandwiched between the positive electrode and the negative electrode, and an electrolyte solution disposed between the positive electrode and the negative electrode.
[0307] Figure 1 2 is a schematic diagram showing an example of a lithium secondary battery. For example, a cylindrical lithium secondary battery 10 is manufactured as follows.
[0308] First, if Figure 1 As shown in the partially enlarged view, an electrode group 4 is made by stacking and winding a pair of strip-shaped separators 1, a strip-shaped positive electrode 2 with a positive electrode lead 21 at one end, and a strip-shaped negative electrode 3 with a negative electrode lead 31 at one end in the order of separator 1, positive electrode 2, separator 1, and negative electrode 3.
[0309] As an example, the positive electrode 2 has a positive electrode active material layer 2a including CAM and a positive electrode collector 2b having the positive electrode active material layer 2a formed on one side. Such a positive electrode 2 can be manufactured by first preparing a positive electrode mixture including CAM, a conductive material and a binder, and supporting the positive electrode mixture on one side of the positive electrode collector 2b to form the positive electrode active material layer 2a.
[0310] For example, the negative electrode 3 may be an electrode in which a negative electrode mixture containing a negative electrode active material (not shown) is supported on a negative electrode current collector, or an electrode formed solely of a negative electrode active material, and may be manufactured in the same manner as the positive electrode 2 .
[0311] Next, after the electrode group 4 and the insulator (not shown) are housed in the battery can 5, the bottom of the can is sealed so that the electrolyte 6 is impregnated into the electrode group 4 and the electrolyte is arranged between the positive electrode 2 and the negative electrode 3. Furthermore, the upper part of the battery can 5 is sealed with a top insulator 7 and a sealing body 8, thereby manufacturing a lithium secondary battery 10.
[0312] Examples of the shape of the electrode group 4 include a columnar shape in which the cross-sectional shape of the electrode group 4 when cut in a direction perpendicular to the winding axis is a circle, an ellipse, a rectangle, or a rectangle with rounded corners.
[0313] The shape of the lithium secondary battery having the electrode group 4 may be a shape specified in IEC60086 or JIS C8500, which are battery standards specified by the International Electrotechnical Commission (IEC). For example, a cylindrical shape or a square shape may be used.
[0314] Furthermore, the lithium secondary battery is not limited to the above-mentioned winding type structure, and can also be a stacked structure obtained by repeatedly stacking the positive electrode, separator, negative electrode, and separator. As a stacked lithium secondary battery, a so-called coin-type battery, a button-type battery, or a paper-type (or sheet-type) battery can be exemplified.
[0315] Regarding the positive electrode, separator, negative electrode, and electrolyte that constitute the lithium secondary battery, for example, the structures, materials, and manufacturing methods described in paragraphs 0113 to 0140 of WO2022 / 113904A1 can be used.
[0316] <All-solid-state lithium secondary battery>
[0317] The CAM of this embodiment can be used as a CAM of an all-solid-state lithium secondary battery.
[0318] Figure 2 It is a schematic diagram showing an example of an all-solid-state lithium secondary battery. Figure 2 The all-solid lithium secondary battery 1000 shown has a stacked body 100 having a positive electrode 110, a negative electrode 120 and a solid electrolyte layer 130, and an outer casing 200 for accommodating the stacked body 100. In addition, the all-solid lithium secondary battery 1000 may be a bipolar structure in which CAM and a negative electrode active material are arranged on both sides of a current collector. As a specific example of the bipolar structure, for example, the structure described in JP-A-2004-95400 can be cited.
[0319] The positive electrode 110 has a positive electrode active material layer 111 and a positive electrode collector 112. The positive electrode active material layer 111 includes the above-mentioned CAM and a solid electrolyte. In addition, the positive electrode active material layer 111 may include a conductive material and a binder.
[0320] The negative electrode 120 includes a negative electrode active material layer 121 and a negative electrode current collector 122. The negative electrode active material layer 121 includes a negative electrode active material. In addition, the negative electrode active material layer 121 may include a solid electrolyte and a conductive material.
[0321] The laminate 100 may include an external terminal 113 connected to the positive electrode current collector 112 and an external terminal 123 connected to the negative electrode current collector 122. In addition, the all-solid lithium secondary battery 1000 may include a separator between the positive electrode 110 and the negative electrode 120.
[0322] The all-solid lithium secondary battery 1000 further includes an insulator (not shown) that insulates the stacked body 100 from the outer case 200 , and a sealing body (not shown) that seals the opening 200 a of the outer case 200 .
[0323] The outer shell 200 may be a container formed of a metal material having high corrosion resistance such as aluminum, stainless steel or nickel-plated steel. Alternatively, the outer shell 200 may be a container formed of a laminate film having at least one surface subjected to corrosion resistance treatment and processed into a bag shape.
[0324] Examples of the shape of the all-solid lithium secondary battery 1000 include a coin shape, a button shape, a paper shape (or a sheet shape), a cylindrical shape, a square shape, and a laminated shape (a bag shape).
[0325] The all-solid lithium secondary battery 1000 is shown as an example having one stack 100 , but the present embodiment is not limited thereto. The all-solid lithium secondary battery 1000 may be a structure in which the stack 100 is a unit cell and a plurality of unit cells (stacks 100 ) are enclosed in an outer shell 200 .
[0326] Regarding the all-solid-state lithium secondary battery, for example, the structure, materials, and manufacturing method described in paragraphs 0151 to 0181 of WO2022 / 113904A1 can be used.
[0327] In the lithium secondary battery having the above structure, since the CAM of the present embodiment is used, it is possible to provide a lithium secondary battery capable of maintaining the discharge capacity even when charge and discharge are repeated.
[0328] Furthermore, since the positive electrode having the above-described structure includes the CAM having the above-described structure, the discharge capacity can be maintained even when the lithium secondary battery is repeatedly charged and discharged.
[0329] Furthermore, since the lithium secondary battery having the above-described structure has the above-described positive electrode, it is a secondary battery capable of maintaining a discharge capacity even when charge and discharge are repeated.
[0330] The preferred embodiments of the present invention have been described above with reference to the accompanying drawings, but the present invention is not limited to the above examples. The various shapes and combinations of the components shown in the above examples are only examples, and various changes can be made based on design requirements within the scope of the present invention.
[0331] Furthermore, the present invention may include the following aspects.
[0332]
[21] A CAM comprising secondary particles as aggregates of primary particles, having a layered structure, and comprising the aforementioned element M1 and the aforementioned element M2, satisfying the following (1) and (2).
[0333] (1) The aforementioned α is 0.70-0.96.
[0334] (2) The aforementioned β is 0.08-0.18.
[0335]
[22] The CAM according to
[21] , wherein the grain boundaries between the primary particles in the cross section of the secondary particles observed using a transmission electron microscope-energy dispersive X-ray spectroscopy method have a portion enriched in the element M1.
[0336]
[23] The CAM according to
[21] or
[22] , wherein the content of Mn is 0.03-0.7 mol relative to 1 mol of the total amount of the aforementioned element M2.
[0337]
[24] The CAM according to any one of
[21] to
[23] , which is represented by the aforementioned composition formula (I).
[0338]
[25] A CAM according to any one of
[21] to
[24] , wherein the S Li It is 1.6-3.4.
[0339]
[26] A CAM according to any one of
[21] to
[25] , wherein the I Li Is 14-40.
[0340]
[27] The CAM according to any one of
[21] to
[26] , wherein the BET specific surface area is 0.4-1.5 m 2 / g.
[0341]
[28] A CAM according to any one of
[21] to
[27] , wherein D 10 , D 50 and D 90 Satisfies the above (II)-2.
[0342]
[29] The CAM according to any one of
[21] to
[28] , which is for use in a solid-state lithium secondary battery.
[0343]
[30] An electrode for a lithium secondary battery, comprising the CAM described in any one of
[21] to
[29] .
[0344]
[31] A lithium secondary battery comprising the lithium secondary battery electrode described in
[30] .
[0345] Example
[0346] Hereinafter, the present invention will be described by way of examples, but the present invention is not limited to these examples.
[0347] <Determination of α and β>
[0348] α and β were measured by performing XPS analysis of CAM according to the methods described in the above [Measurement method of α] and [Measurement method of β].
[0349] <S Li and I Li Determination
[0350] Perform XPS analysis of CAM by the methods described in the above [α determination method] and [β determination method], and determine S Li and I Li .
[0351] <Confirmation method for enrichment part>
[0352] Obtain a cross-section of CAM by the method described in the above [Cross-section acquisition method], perform TEM analysis, and confirm according to the method described in [Confirmation method for enrichment part].
[0353] <Composition analysis of CAM>
[0354] Perform composition analysis of CAM by the method described in the above [Composition analysis].
[0355] [Determination of BET specific surface area]
[0356] Perform specific surface area analysis of CAM by the method described in the above [Determination of BET specific surface area].
[0357] By the above [D 10 , D 90 and D 50 Determination] described method to implement D 10 , D 90 and D 50的 Analysis.
[0358] <Confirmation method for layered structure>
[0359] Confirm whether CAM has a layered structure by the method described in the above [Confirmation method for layered structure].
[0360] Manufacture a solid-state lithium-ion secondary battery by the method described in the above [Measurement of initial discharge capacity]. For the manufactured solid-state lithium secondary battery, perform a charge-discharge test by the method described in the above <Charge-discharge test>, and evaluate the battery performance based on the value of the discharge capacity.
[0361] <Example 1>
[0362] (Manufacture of CAM1)
[0363] After adding water into a reaction tank equipped with a stirrer and an overflow pipe, add an aqueous sodium hydroxide solution and keep the liquid temperature at 50 °C.
[0364] A nickel sulfate aqueous solution, a cobalt sulfate aqueous solution and a manganese sulfate aqueous solution were mixed at a molar ratio of Ni to Co to Mn of 0.6:0.2:0.2 to prepare a mixed raw material solution 1.
[0365] Next, the mixed raw material solution 1 and the ammonium sulfate aqueous solution as a complexing agent were continuously added to the reaction tank under stirring. When the pH of the mixed solution in the reaction tank reached 12.1 (when the temperature of the aqueous solution was 40° C.), the sodium hydroxide aqueous solution was added dropwise at an appropriate time to obtain a reaction precipitate.
[0366] The obtained reaction precipitate was washed, dehydrated with a centrifugal separator, washed, dehydrated, separated, and dried at 105° C. for 20 hours to obtain MCC1 as a nickel-cobalt-manganese composite hydroxide.
[0367] (Preparation process of coating material raw material 1)
[0368] 133 g of 30% by mass H2O2 water, 151 g of pure water, and 6.8 g of niobium oxide hydrate Nb2O5·3H2O (content 72% by mass) were mixed. Then, 13 g of 28% by mass ammonia water was added and stirred. Furthermore, 1.9 g of LiOH·H2O was added to obtain a coating material raw material 1 containing Nb.
[0369] Using a tumbling flow apparatus (MP-01 manufactured by Powrex Corporation), the coating material raw material 1 was sprayed onto the MCC 1 at a ratio of Nb / (Ni+Co+Mn)=1 mol%.
[0370] Then, lithium hydroxide monohydrate powder was further weighed and mixed so as to achieve a molar ratio of Li / (Ni+Co+Mn)=1.03, and primary calcination was performed at 650° C. for 5 hours in an oxygen atmosphere.
[0371] Next, main calcination was performed at 840° C. for 5 hours in an oxygen atmosphere, thereby obtaining a main calcined product 1 .
[0372] The obtained main burned product 1 was pulverized by a Masscolloider type pulverizer to obtain a pulverized product 1.
[0373] The crushed product 1 was dried at 120°C for 10 hours in a vacuum atmosphere. Then, the coating material raw material 1 was sprayed on the crushed product 1 at a ratio of Nb / (Ni+Co+Mn)=0.61 mol% using the above-mentioned tumbling flow device. At this time, the flow rate of the high-pressure air in the two-fluid spray nozzle of the above-mentioned tumbling flow device was 30 NL / min.
[0374] (Heat treatment process)
[0375] The pulverized product 1 onto which the coating material raw material 1 was sprayed was heat treated at 200° C. for 5 hours in an oxygen atmosphere to obtain a CAM 1 .
[0376] [CAM1's review]
[0377] The α value of CAM1 is 0.79, and the β value is 0.13. The BET specific surface area is 0.5 m 2 / g. (D 90 -D 10 ) / D 50 The content of Mn is 0.56. The content of Mn is 0.20 mol relative to the total amount of element M2. The discharge capacity of the solid lithium secondary battery of CAM1 is 176 mAh / g. CAM1 has a layered structure. The x, a, b, c, d, e, δ, element M1, element M2, element Z, S in the composition formula (I) of CAM1 are Li and I Li The presence or absence of the enrichment section is recorded in Table 1. The following Examples and Comparative Examples are also recorded in the same Table 1.
[0378] <Example 2>
[0379] (CAM2 Manufacturing)
[0380] MCC1 and lithium hydroxide monohydrate powder were weighed and mixed at a molar ratio of Li / (Ni+Co+Mn)=1.03, and then primary calcined at 650°C for 5 hours in an oxygen atmosphere to obtain a primary calcined product 2.
[0381] Using the same rotating flow device as in Example 1, the coated material raw material 1 is sprayed onto the primary sintered product 2 at a ratio of Nb / (Ni+Co+Mn)=1mol%, and then the main sintering is carried out at 860°C for 5 hours in an oxygen atmosphere to obtain the main sintered product 2.
[0382] The obtained main burned product 2 was pulverized by a Masscolloider type pulverizer to obtain a pulverized product 2.
[0383] The crushed product 2 was dried at 120°C for 10 hours in a vacuum atmosphere. Next, the coating material raw material 1 was sprayed on the crushed product 2 at a ratio of Nb / (Ni+Co+Mn)=0.48 mol% using the above-mentioned tumbling flow device. At this time, the flow rate of the high-pressure air in the two-fluid spray nozzle of the above-mentioned tumbling flow device was 30 NL / min.
[0384] (Heat treatment process)
[0385] The pulverized product 2 onto which the coating material raw material 1 was sprayed was heat treated at 200° C. for 5 hours in an oxygen atmosphere to obtain a CAM 2 .
[0386] [CAM2 review]
[0387] The α value of CAM2 is 0.74, and the β value is 0.09. The BET specific surface area is 0.4 m 2 / g. (D 90 -D 10 ) / D 50 The content of Mn is 0.19 mol relative to the total amount of element M2 (1 mol). The discharge capacity of the solid lithium secondary battery of CAM2 is 179 mAh / g. CAM2 has a layered structure.
[0388] <Example 3>
[0389] (CAM3 Manufacturing)
[0390] (Preparation process of coating material raw material 2)
[0391] 3300 g of pure water and 100 g of tungsten oxide WO3 were mixed, and 110 g of LiOH.H2O was further added to obtain a coating material raw material 2 containing W.
[0392] Using the same tumbling fluidization apparatus as in Example 1, the coating material raw material 2 was sprayed onto MCC1 at a ratio of W / (Ni+Co+Mn)=1 mol%.
[0393] Lithium hydroxide monohydrate powder was further weighed and mixed at a molar ratio of Li / (Ni+Co+Mn)=1.03, and then primary calcination was performed at 650°C for 5 hours in an oxygen atmosphere. Subsequently, main calcination was performed at 840°C for 5 hours in an oxygen atmosphere to obtain main calcined product 3.
[0394] The obtained main burned product 3 was pulverized by a Masscolloider type pulverizer to obtain a pulverized product 3.
[0395] The crushed product 3 was dried at 120°C for 10 hours in a vacuum atmosphere. Then, the coating material raw material 1 was sprayed on the crushed product 3 at a ratio of Nb / (Ni+Co+Mn)=0.99 mol% using the above-mentioned tumbling flow device. At this time, the flow rate of the high-pressure air in the two-fluid spray nozzle of the above-mentioned tumbling flow device was 30 NL / min.
[0396] (Heat treatment process)
[0397] The pulverized product 3 onto which the coating material raw material 1 was sprayed was heat treated at 200° C. for 5 hours in an oxygen atmosphere to obtain a CAM 3.
[0398] [CAM3 evaluation]
[0399] The α value of CAM3 is 0.87, and the β value is 0.15. The BET specific surface area is 0.4 m 2 / g. (D 90 -D 10 ) / D 50 The content of Mn is 0.20 mol relative to the total amount of element M2. The discharge capacity of the solid lithium secondary battery of CAM3 is 175 mAh / g. CAM3 has a layered structure.
[0400] <Comparative Example 1>
[0401] (CAM-C1 manufacturing)
[0402] MCC1 and lithium hydroxide monohydrate powder were weighed and mixed at a molar ratio of Li / (Ni+Co+Mn)=1.03, and then primary calcined at 650°C for 5 hours in an oxygen atmosphere to obtain a primary calcined product C1.
[0403] The coating material raw material 1 was sprayed onto the primary fired product C1 at a ratio of Nb / (Ni+Co+Mn)=1 mol% using the same tumbling fluidization device as in Example 1. Then, main firing was performed at 860°C for 5 hours in an oxygen atmosphere to obtain a main fired product C1.
[0404] The obtained main burned product C1 was pulverized by a Masscolloider type pulverizer to obtain CAM-C1.
[0405] [CAM-C1 review]
[0406] The α value of CAM-C1 is 0.20, and the β value is 0.04. The BET specific surface area is 0.4 m 2 / g. (D 90 -D 10 ) / D 50 The content of Mn is 0.19 mol relative to the total amount of element M2. The discharge capacity of the solid lithium secondary battery of CAM-C1 is 161 mAh / g. CAM-C1 has a layered structure.
[0407] <Comparative Example 2>
[0408] (CAM-C2 manufacturing)
[0409] The coating material raw material 1 was sprayed onto MCC1 at a ratio of Nb / (Ni+Co+Mn)=1 mol% using the same tumbling flow apparatus as in Example 1. Furthermore, lithium hydroxide monohydrate powder was weighed and mixed at a molar ratio of Li / (Ni+Co+Mn)=1.03, and then primary calcination was performed at 650°C for 5 hours in an oxygen atmosphere.
[0410] Next, main calcination was performed at 840° C. for 5 hours in an oxygen atmosphere to obtain a main calcined product C2.
[0411] The obtained main fired product was pulverized by a Masscolloider type pulverizer to obtain CAM-C2.
[0412] [CAM-C2 evaluation]
[0413] The α value of CAM-C2 is 0.08, and the β value is 0.02. The BET specific surface area is 0.7 m 2 / g. (D 90 -D 10 ) / D 50 The content of Mn is 0.20 mol relative to the total amount of element M2. The discharge capacity of the solid lithium secondary battery of CAM-C2 is 152 mAh / g. CAM-C2 has a layered structure.
[0414] <Comparative Example 3>
[0415] (CAM-C3 manufacturing)
[0416] MCC1 and lithium hydroxide monohydrate powder were weighed and mixed at a molar ratio of Li / (Ni+Co+Mn)=1.03, and then primary calcined at 650°C for 5 hours in an oxygen atmosphere. Subsequently, main calcination was performed at 840°C for 5 hours in an oxygen atmosphere to obtain main calcined product C3.
[0417] The obtained main burned product C3 was pulverized by a Masscolloider type pulverizer to obtain a pulverized product C3.
[0418] The crushed product C3 was dried at 120°C for 10 hours in a vacuum atmosphere. The coating material raw material 1 was sprayed on the crushed product C3 at a ratio of Nb / (Ni+Co+Mn)=1.5 mol% using the same tumbling flow device as in Example 1. At this time, the flow rate of the high-pressure air in the two-fluid spray nozzle of the tumbling flow device was 100 NL / min.
[0419] (Heat treatment process)
[0420] The pulverized product C3 sprayed with the coating material raw material 1 was heat treated at 200° C. for 5 hours in an oxygen atmosphere to obtain CAM-C3.
[0421] [CAM-C3 evaluation]
[0422] The α value of CAM-C3 is 0.42, and the β value is 0.05. The BET specific surface area is 2.4 m 2 / g. (D 90 -D 10 ) / D 50 The content of Mn is 0.19 mol relative to the total amount of element M2. The discharge capacity of the solid lithium secondary battery of CAM-C3 is 171 mAh / g. CAM-C3 has a layered structure.
[0423] <Comparative Example 4>
[0424] (CAM-C4 manufacturing)
[0425] MCC1 and lithium hydroxide monohydrate powder were weighed and mixed at a molar ratio of Li / (Ni+Co+Mn)=1.03, and then primary calcined at 650°C for 5 hours in an oxygen atmosphere. Subsequently, main calcination was performed at 840°C for 5 hours in an oxygen atmosphere to obtain main calcined product C4.
[0426] The obtained main burned product C4 was pulverized by a Masscolloider type pulverizer to obtain a pulverized product C4.
[0427] The crushed product C4 was dried at 120°C for 10 hours in a vacuum atmosphere. The coating material raw material 1 was sprayed on the crushed product C4 at a ratio of Nb / (Ni+Co+Mn)=0.80 mol% using the same tumbling flow device as in Example 1 to obtain CAM-C4. At this time, the amount of high-pressure air in the two-fluid spray nozzle of the tumbling flow device was 30 NL / min.
[0428] [CAM-C4 review]
[0429] The α value of CAM-C4 is 0.64, and the β value is 0.07. The BET specific surface area is 1.0 m 2 / g. (D 90 -D 10 ) / D 50 The content of Mn is 0.22 mol relative to the total amount of element M2 (1 mol). The discharge capacity of the solid lithium secondary battery of CAM-C4 is 171 mAh / g. CAM-C4 has a layered structure.
[0430] The physical properties and compositions of Examples 1 to 3 and Comparative Examples 1 to 4 are shown in Table 1 below.
[0431]
[0432] In Examples 1 to 3 manufactured by a method including a manufacturing step (A) or a manufacturing step (B), and a step of mixing the obtained calcined product with a coating material raw material, α and β of CAM meet the scope of the present invention, and element M1 and element M2 exist at a specific ratio on the surface of the secondary particle and inside the secondary particle. It was confirmed that when such a CAM is used, the initial discharge capacity of the lithium secondary battery is 172 mAh / g or more.
[0433] Regarding Comparative Examples 1 and 2 manufactured without performing the manufacturing step (A) or the manufacturing step (B), and Comparative Examples 3 and 4 manufactured without mixing the calcined product with the coating material raw material, α and β of the CAM do not meet the range of the present invention. It was confirmed that when such a CAM is used, the initial discharge capacity of the lithium secondary battery is about 150 to 170 mAh / g.
[0434] Explanation of symbols
[0435] 1: separator, 2: positive electrode, 2a: positive electrode active material layer, 2b: positive electrode collector layer, 3: negative electrode, 4: electrode group, 5: battery can, 6: electrolyte, 7: top insulator, 8: sealing body, 10: lithium secondary battery, 21: positive electrode lead, 31: negative electrode lead, 100: laminate, 110: positive electrode, 111: positive electrode active material layer, 112: positive electrode collector, 113: external terminal, 120: negative electrode, 121: negative electrode active material layer, 122: negative electrode collector, 123: external terminal, 130: solid electrolyte layer, 200: outer shell, 200a: opening, 1000: all-solid-state lithium secondary battery.
Claims
1. A positive electrode active material for a lithium secondary battery, the positive electrode active material for a lithium secondary battery comprising secondary particles which are aggregates of primary particles and having a layered structure, and comprising element M1 and element M2, wherein the element M1 is at least one element selected from the group consisting of Nb, W, Mo, Ta, La, B, and P, the element M2 is at least one element selected from the group consisting of Ni, Co, and Mn, the positive electrode active material for a lithium secondary battery satisfies the following (1) and (2): (1) The atomic concentration (atomic %) of the element M1 present on the surface of the secondary particles obtained by X-ray photoelectron spectroscopy (XPS), relative to the total amount of the atomic concentration (atomic %) of the element M1 and the atomic concentration (atomic %) of the element M2 present on the surface of the secondary particles, i.e., α, is 0.6 or more and 1 or less; (2) The atomic concentration (atomic %) of the element M1 present inside the secondary particles obtained by the X-ray photoelectron spectroscopy (XPS) analysis, relative to the total amount of the atomic concentration (atomic %) of the element M1 and the atomic concentration (atomic %) of the element M2 present inside the secondary particles, i.e., β, is 0.08 or more and 0.20 or less.
2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the grain boundary of the primary particles in the cross section of the secondary particles observed by transmission electron microscopy - energy dispersive X-ray spectroscopy has an enrichment portion of the element M1.
3. The positive electrode active material for lithium secondary battery according to claim 1 or 2, wherein The content of Mn is 0.03 mol or more relative to 1 mol of the total amount of the element M2.
4. The positive electrode active material for a lithium secondary battery according to claim 1 or 2, which is represented by the following compositional formula (I): Li x (Ni a Co b Mr c Z d M1 e )O δ (I), The compositional formula (I) satisfies 0.98 ≤ x ≤ 1.80, 0.3 < a ≤ 1, 0 ≤ b ≤ 0.3, 0.03 ≤ c ≤ 0.7, 0 ≤ d ≤ 0.05, 0 < e ≤ 0.05, a + b + c + d + e = 1, and 2 ≤ δ < 3, Z is at least one element selected from the group consisting of Al, Zr, and Ti, and M1 is at least one element selected from the group consisting of Nb, W, Mo, Ta, La, B, and P.
5. The positive electrode active material for lithium secondary batteries according to claim 1 or 2, wherein the ratio of the atomic concentration of Li present on the surface of the secondary particles to the atomic concentration of the element M1 present on the surface of the secondary particles obtained by the X-ray photoelectron spectroscopy (XPS) analysis is S Li It is greater than or equal to 1 and less than or equal to 4.
6. The positive electrode active material for a lithium secondary battery according to claim 1 or 2, wherein the ratio of the atomic concentration of Li present in the interior of the secondary particle to the atomic concentration of the element M1 present in the interior of the secondary particle obtained by the X-ray photoelectron spectroscopy (XPS) analysis is Li It is 10 or more and 50 or less.
7. The positive electrode active material for lithium secondary battery according to claim 1 or 2, wherein the BET specific surface area is 0.2 m 2 / g or more and 2m 2 / g or less.
8. The positive electrode active material for lithium secondary battery according to claim 1 or 2, wherein D 10 , D 50 and D 90 Satisfy the following (II): (D 90 -D 10 ) / D 50 ≤1.0(II), D 10 The cumulative volume particle size of the positive electrode active material for the lithium secondary battery is 10%, D 50 The 50% cumulative volume particle size of the positive electrode active material for the lithium secondary battery, D 90 The particle size is 90% of the cumulative volume of the positive electrode active material for the lithium secondary battery.
9. The positive electrode active material for a lithium secondary battery according to claim 1 or 2, which is for a solid-state lithium secondary battery.
10. An electrode for a lithium secondary battery, which comprises the positive electrode active material for a lithium secondary battery according to claim 1 or 2.
11. A lithium secondary battery, which comprises the electrode for a lithium secondary battery according to claim 10.
Citation Information
Patent Citations
High density nickel hydroxide coprecipitated with cobalt and manganese, and method for producing the same
JP2002201028A
Bipolar battery and its control method
JP2004095400A
Material for positive electrode active material
JP2010170715A
Information processing device
JP2022142158A
Method for producing lithium metal composite oxide
WO2022113904A1